High N, dry: Experimental nitrogen deposition exacerbates native shrub loss and nonnative plant invasion during extreme drought. (19th April 2017) - Valliere, Justin M.; Irvine, Irina C.; Santiago, Louis; Allen, Edith B.
Abstract: Hotter, longer, and more frequent global change‐type drought events may profoundly impact terrestrial ecosystems by triggering widespread vegetation mortality. However, severe drought is only one component of global change, and ecological effects of drought may be compounded by other drivers, such as anthropogenic nitrogen (N) deposition and nonnative plant invasion. Elevated N deposition, for example, may reduce drought tolerance through increased plant productivity, thereby contributing to drought‐induced mortality. High N availability also often favors invasive, nonnative plant species, and the loss of woody vegetation due to drought may create a window of opportunity for these invaders. We investigated the effects of multiple levels of simulated N deposition on a Mediterranean‐type shrubland plant community in southern California from 2011 to 2016, a period coinciding with an extreme, multiyear drought in the region. We hypothesized that N addition would increase native shrub productivity, but that this would increase susceptibility to drought and result in increased shrub loss over time. We also predicted that N addition would favor nonnatives, especially annual grasses, leading to higher biomass and cover of these species. Consistent with these hypotheses, we found that high N availability increased native shrub canopy loss and mortality, likely due to the higher productivity and leaf area and reduced water‐use efficiency we observed in shrubs subject to N addition. As native shrub cover declined, we also observed a concomitant increase in cover and biomass of nonnative annuals, particularly under high levels of experimental N deposition. Together, these results suggest that the impacts of extended drought on shrubland ecosystems may be more severe under elevated N deposition, potentially contributing to the widespread loss of native woody species and vegetation‐type conversion. Abstract : Extreme drought events may have a profound impact on ecosystems by triggering widespread vegetation loss, and this may be compounded by other drivers of global change such as nitrogen deposition and nonnative plant invasion. We explored how experimental N deposition influenced native and invasive plant species of a Mediterranean shrubland in southern California during a multiyear drought. We found that nitrogen addition exacerbated shrub loss and invasion during extended drought, which has important implications for the conservation of ecosystems under future global change.